Hyaluronidase and pH Dual-Responsive Nanoparticles for Targeted Breast Cancer Stem Cells - Li, Weinan; Zhang, Xiaoyu; Nan, Yang; Jia, Li; Sun, Jialin; Zhang, Lina; Wang, Yanhong (Frontiers in Oncology, 2021)
pH-responsive and CD44 receptor-mediated targeted nanoparticles for eliminating cancer stem cells (CSCs) were developed based on complexes of PEG-poly(β-amino ester) (PEG-PBAE) micelles (PPM) coated with hyaluronic acid (HA) (HA-coated PPM complex, or HPPMc). Thioridazine (Thz) was loaded into HPPMc with a decent drug loading content. The release results of the drug in vitro showed that Thz was released from the HPPMc, which was stimulated by both the acidic pH and specific enzymes. Cytotoxicity studies on mammospheres (MS) revealed that the toxicity potential of Thz-loaded HPPMc (Thz–HPPMc) at pH 5.5 was better than drug solutions. Compared with that at pH 7.4, a higher cellular uptake of a coumarin-6 (C6)-labeled complex at pH 5.5 was observed, which demonstrated that complexes were efficiently taken up in MS. Meanwhile, free HA competitively inhibited the cellular uptake of HPPMc, which revealed that the uptake mechanism was CD44 receptor-mediated endocytosis. Within the acidic endolysosomal environment, the protonation of PBAE facilitated the escape of the complex from the lysosome and releases the drug. The results of in vivo distribution studies and tumor suppression experiments showed that HPMMc could stay in the tumor site of BALB/c nude mice for a longer period of time, and Thz–HPPMc could significantly improve the tumor-suppressing effect. All these results demonstrated the great potential of the multifunctional nanoparticle system for eliminating CSCs.